Social Media Influencer (SMI) restaurant reviews and students’ patronization decision / Abdul Malik Philip ... [et al.] - Philip, Abdul Malik; Othman, Zulhan; Talib, Adi Hakim; Saiful Bakhtiar, Mohd Faeez; Kedin, Nor Adila (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Social Media Influencers (or SMI) has access to a wide audience and they can persuade others by virtue of their authenticity and reach. While there is a significant link between SMI review and consumer purchase decision within the restaurant industry, it is unclear to what extent this finding would be consistent specifically among university students. In accessing the influence of SMI restaurant reviews (covering food quality, food variety, environment and location) towards university students’ patronization decision, a quantitative research approach was employed using self-administered survey. A total of 151 usable responses were obtained from undergraduate students at the Faculty of Hotel and Tourism Management (FHTM) in Universiti Teknologi MARA. It was found that the four components of SMI restaurant reviews had significant positive relationship towards university students’ patronization decision. It is recommended to restaurant owners to engage their businesses actively in social media marketing to attract adolescents such as university students. SMI restaurant reviews that primarily aimed at similar target group is encouraged to emphasize on food variety as it is perceived the most influential factor; and subsequently followed by the premise environment, food quality offered and finally the location.